Evaluation of perfusion index as an objective indicator of successful interscalene block - Pardeep Kumar; Arora, Vandna; Akanksha Khatri; Suresh Kumar Singhal; Shikha Madan (Asian Journal of Medical Sciences, 2023)
Background: Interscalene nerve blocks are commonly performed for surgeries of the upper limb. Assessment methods for evaluation of blocks are conventional and subjective. Aims and Objectives: The aim of the study was to evaluate perfusion index (PI) as an objective indicator for assessing successful ultrasound guided interscalene block. Materials and Methods: This prospective, observational study included adult patients undergoing upper limb surgery (humerus and shoulder) under USG guided interscalene nerve block. PI was recorded at baseline (before LA administration), at every 2 min till 10 min, and then every 5 min till 30 min after the block in both the arms. The PI values were compared between the blocked and unblocked arms at all observed time points. PI ratio was calculated as the ratio between PI at 15 min after block and the baseline PI. Results: The PI increased significantly in the blocked limb after local anesthetic injection and there was a statistically significant difference in PI values between the blocked and unblocked arms at all-time points. Both PI and PI ratio at 15 min after injection showed a sensitivity and specificity of 100% for block success at cutoff values of 3.2 and 2.04, respectively. Conclusion: PI maybe used as an objective indicator of successful interscalene nerve block. PI >3.2 and PI ratio >2.04 at 15 min are accurate predictors for block success.